21. SURVEYING THE NEED TO CHOOSE COSMETIC SERVICES AND SOME INFLUENCING FACTORS OF COSMETIC SERVICES FOR CUSTOMERS IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2024)
The research aims to survey the need to choose cosmetic services and some influencing factors on Ho Chi Minh City customers.Objective: Survey on the need to choose cosmetic services and some influencing factors of cosmetic services on customers in Ho Chi Minh City.Research method: Research design: Descriptive cross-sectional study. Time from June - September 2020. Research subjects: Customers visiting hospitals specializing in cosmetic surgery and clinics specializing in cosmetic surgery licensed by the Ministry of Health and the Department of Health of Ho Chi Minh City. Convenience sampling method. Research sample: 423 customers.Result: Survey results of 423 customers using cosmetic services in Ho Chi Minh City in 2020 showed: Regarding customer characteristics: Female customers account for 65.2%, higher than male customers at 34.8%. Most customers are 25-39 years old, accounting for 44.9%, and 68.1% have a residential address in Ho Chi Minh City. The single rate is 43.7%, and the married rate is 42.6%. Customers with a university degree or higher account for 57.7%. Among them, office workers account for the highest proportion at 19.1%, businesspeople at 18.7%, and artists at only 16.1%. Regarding customers' need to choose and use cosmetic services, most customers intend to use cosmetic services because they want to improve their appearance, 91.72%, and because of social trends. Modern accounts for 91.49%. Influencing factors of different types of cosmetic services: This shows that most customers rate the quality of cosmetic services at an elevated level of 4-5 points. The median satisfaction score is 4.23±0.58; The lowest is 1.53 points, and the highest is 4.95 points. The rate of satisfied customers and helpful reviews with cosmetic services is 76.6%.Conclusion: Results of a survey of 423 customers in Ho Chi Minh City in 2020 with the following conclusion: Most customers intend to use cosmetic services because they want to improve their appearance 91.72% and because of social trends. Modern society accounts for 91.49%, and most customers are satisfied and give helpful reviews to cosmetic services, accounting for 76.6%.
Keywords: Demand; cosmetic services; some influencing factors